Forest Resource Use Pattern in Relation to Socioeconomic Status (A Case Study from Two Altitudinal Zones of Western Himalaya, India) - Singh, Hardeep; Malik, Zubair A.; Baluni, Pratibha (Indian Forester, 2017)
Biomass has been the principal component of domestic energy throughout the Indian Himalayan region. The present study, carried out in two altitudinal zones, explored the forest resource use pattern in relation to the socio economic status of the denizens in a part of Western Himalaya, India. Structured and pretested questionnaires were used to interview approximately 30% of the total households in each village (a total of 143 in 9 villages). The average cultivated land per family was less than 1 ha (0.85). In sub tropical and temperate zones, the average fuelwood and fodder consumption (kg/day/household) was found to be 14.93 and 63.80 and 13.16 and 60.42 respectively. Statistical analysis showed significant variation of fuelwood and fodder consumption in the two altitudinal zones (P < 0.000, t-test; n= 143 and df= 142). Alternative fuels (kerosene and LPG) are used occasionally. More than 70% of biomass is extracted from the forests and a total of 30 tree species are frequently lopped for this purpose. The pressure exerted by human and bovine populations, coupled with unsustainable management policies has resulted in the destruction of forest cover and ecological degradation. Support and active participation of local people is mandatory for conservation of these forests.